Compression at Myofascial Trigger Point on Chronic Neck Pain Provides Pain Relief through the Prefrontal Cortex and Autonomic Nervous System: A Pilot Study - Morikawa, Yoshiki; Takamoto, Kouich; Nishimaru, Hiroshi; Taguchi, Toru; Urakawa, Susumu; Sakai, Shigekazu; Ono, Taketoshi; Nishijo, Hisao (Frontiers in Neuroscience, 2017)
Compression at myofascial trigger points (MTrPs), known as ‘ischemic compression’, has been reported to provide immediate relief of musculoskeletal pain and reduce the sympathetic activity that exacerbates chronic pain. We conducted a pilot study to investigate the possible involvement of the prefrontal cortex in pain relief obtained by MTrP compression in the present study, we analyzed the relationships among prefrontal hemodynamic activity, activity of the autonomic nervous system, and subjective pain in patients with chronic neck pain, with and without MTrP compression. Twenty-one female subjects with chronic neck pain were randomly assigned to two groups: MTrP compression (n = 11) or Non-MTrP compression (n = 10). Compression for 30 s was conducted 4 times. During the experiment, prefrontal hemodynamic activity [changes in Oxy-hemoglobin (Hb), Deoxy-Hb, and Total-Hb concentrations] and autonomic activity based on heart rate variability were monitored by using near infrared spectroscopy (NIRS) and electrocardiography (ECG), respectively. The results indicated that MTrP compression significantly reduced subjective pain compared with Non-MTrP compression. The spectral frequency-domain analyses of heart rate variability (HRV) indicated that a low frequency (LF) component of HRV was decreased, and a high frequency (HF) component of HRV was increased during MTrP compression, while LF/HF ratio was decreased during MTrP compression. In addition, prefrontal hemodynamic activity was significantly decreased during MTrP compression compared with Non-MTrP compression. Furthermore, changes in autonomic activity were significantly correlated with changes in subjective pain and prefrontal hemodynamic activity. Along with previous studies indicating a role for sympathetic activity in the exacerbation of chronic pain, the present results suggest that MTrP compression in the neck region alters the activity of the autonomic nervous system via the prefrontal cortex to reduce subjective pain.